Las Bartramiaceae (Musci) del Valle de México, México - Cárdenas S., Ángeles (Instituto de Ecología, A.C., 2000)
A list of the members of the family Bartramiaceae occuring in the Valley of Mexico is presented. The family is represented in the area by 12 species amounting to 39 per cent of those recorded (31 species) for the country. Habitat data and other pertinent information is provided for all specimens examined. Members of this family grow mostly on soil and rocks, at intermediate or high elevations in almost all types of vegetation known in the area of study.